OP0274-HPR A functional exercise program improves pain and health related quality of life in patients with fibromyalgia: a randomisedcontrolled trial. (12th June 2018) - Fernandes, G.; Jennings, F.; Cabral, M.; Santos, R.; Natour, J.
Abstract : Background: Fibromyalgia (FM) is a syndrome characterised mainly by chronic generalised pain that affects the physical fitness and functional capacity of patients. There is increasing evidence of the benefits of physical exercise in improving FM symptoms, making these interventions part of therapeutic arsenal. Objectives: To evaluate the effectiveness of a program of functional exercises in reducing pain, improving functional capacity, increasing muscle strength, improving flexibility, balance and quality of life of patients with FM. Methods: It is a controlled and randomised study, with blind evaluator. A total of 82 female patients with FM were included, with age between 18 and 65 years, randomised into two groups, intervention and control. The intervention group (FEG) performed functional exercise training for 45 min twice a week for 14 weeks. The control group (SEG) performed stretching exercises with the same duration and frequency. Evaluation instruments were: VAS – Visual Analogue Scale for pain assessment; FIQ- Fibromyalgia Impact Questionnaire, for assessing health-related quality of life; Time-up and go test for functional performance evaluation; 1RM, for evaluation of muscle strength; Bank of Welss, for the assessment of flexibility; Berg Balance Scale, to evaluate balance; and SF-36 to evaluate general quality of life. Also, the amount of analgesics used during the intervention period was assessed. Results: 41 patients were randomised to the FEG and 41 patients to the SEG. After intervention, the FEG presented a reduction in pain and an improvement in the quality of life related to the disease, which was statistically significant compared to SEG. Regarding general quality of life, functional capacity, muscle strength, flexibility and balance, there was no difference between the groups. Conclusions: Functional exercise training proved to be effective in reducing pain and improving the health-related quality of life of patients with FM when compared to stretching exercises. References: [1] Wolfe F, Clauw D, Fitzcharles MA, Goldenberg D, Katz RS, Mease P, et al. The American College of Rheumatology Preliminary Diagnostic Criteria for Fibromyalgia and Measurement of Symptom Severity. Arthritis Care Res2010;62:600–10. [2] Hauser W, Klose P, Langhorst J, et al. Efficacy of different types of aerobic exercise in fibromyalgia syndrome: A systematic review and meta-analysis of randomised controlled trials. Arthritis Res Ther2010;12:R79. [3] Burchardt CS. Multidisciplinary approaches for management of fibromyalgia. Curr Pharm Des2006;12:59–66. Disclosure of Interest: None declared